Waking up in heaven : a true story of brokenness, heaven, and life again - McVea, Crystal (Howard Books, 2013)
Recounts the story of a young mother who underwent an intense near-death experience after she became unresponsive during a medical emergency, as she discusses the hardships of her past and the impact of the experience on her life.